Tyrosine kinase inhibitors impair B-cell immune responses in CML through off-target inhibition of kinases important for cell signaling - de Lavallade, Hugues (Blood, 2013)
Tyrosine kinase inhibitors (TKIs) have significant off-target multikinase inhibitory effects. We aimed to study the impact of TKIs on the in vivo B-cell response to vaccination. Cellular and humoral responses to influenza and pneumococcal vaccines were evaluated in 51 chronic phase chronic myeloid leukemia (CML) patients on imatinib, or second-line dasatinib and nilotinib, and 24 controls. Following vaccination, CML patients on TKI had significant impairment of IgM humoral response to pneumococcus compared with controls (IgM titer 79.0 vs 200 U/mL, P = .0006), associated with significantly lower frequencies of peripheral blood IgM memory B cells. To elucidate whether CML itself or treatment with TKI was responsible for the impaired humoral response, we assessed memory B-cell subsets in paired samples collected before and after imatinib therapy. Treatment with imatinib was associated with significant reductions in IgM memory B cells. In vitro coincubation of B cells with plasma from CML patients on TKI or with imatinib, dasatinib, or nilotinib induced significant and dose-dependent inhibition of Bruton’s tyrosine kinase and indirectly its downstream substrate, phospholipase-C-γ2, both important in B-cell signaling and survival. These data indicate that TKIs, through off-target inhibition of kinases important in B-cell signaling, reduce memory B-cell frequencies and induce significant impairment of B-cell responses in CML.